DETERMINANTS OF WORKING STATUS OF THE ELDERLY POPULATION IN THE BANGKA BELITUNG ISLANDS PROVINCE - Handayani, Sri Hapsari Murni (EP FEB UNS, 2023)
This study examines the factors influencing employment among the elderly population in the Bangka Belitung Islands, where the elderly population increased by 41,85% from 2010 to 2020, reaching 8,27%. Notably, 45,38% of the elderly were employed in 2020. Using data from the 2020 National Socio-Economic Survey (SUSENAS), this research analyzes individuals aged 60 and above through descriptive analysis and binary logistic regression. The results indicate significant predictors of employment among the elderly include rural residency, being the head of the household, gender, age, and marital status. Specifically, elderly individuals who live in rural areas, are male, currently married, aged 60-69, and are household heads are more likely to be employed. In contrast, poverty status and education level do not significantly impact employment. This study highlights the demographic and social factors that influence the employment tendencies of the elderly, providing insights for policy development to support this population segment.